(untitled) (IITM Journal of Business Studies, 2024)
Social media has become an important tool for spreading knowledge and awareness on various subjects. People are using social media for gaining knowledge as well. Similarly people are using social media for spreading and gaining knowledge about environmental related concern. Environmental concern has become popular term with the growing world. This research provides a brief review about uses of social media for spreading environmental awareness and further how these environmental concern helps in identifying the green purchase behaviour of the consumers. For this study, 250 questionnaires were distributed among the respondents and 205 submitted their response. Linear regression was applied for an analysis of study. The results of the study show that there is significant effect of social media on environmental awareness and environmental awareness on green purchase behaviour. It means social media helps in spreading awareness of environmental issue and concern among individual and this awareness subsequently leads to purchase of green product. Research study is concluded with limitation further scope of study.